What if we could travel without passport? First sight to blockchain-based identity management in tourism - Baser, Mirac Yuecel; Buyukbese, Tuba; Kizildag, Murat (ROUTLEDGE JOURNALS)
Blockchain technology, as a distributed digital ledger, enables users to control their credentials without being breached by third parties. From a tourism perspective, it allows tourists to pass through checkpoints and/or bookings without waiting and having to go through third-party transactions. Hence, this paper aims to discuss traditional identity management (IdM) system challenges and what blockchain might offer as a counterpoint to conventional travel experiences within the
Keywords: digital travel; smart contracts; blockchain technology; digital identity; Identity management